Al-Fahmu al-Lughawiy li Ahadits al-Bid’ah: Dirasah Tahliliyah li Tsalatsah Ahadits Nabawiyah / Linguistic Understanding of Bid'ah Hadiths: An Analytical Study of Three Prophetic Hadiths - Aksa Muhammad Nawawi; Han Han Ulumudin Ismail; Sultan Ahmad Syafe'i; Nun Athirah Syamil (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study starts from the problem of expanding the understanding of the hadiths contained in bid'ah based on the literal reading of some of its words, without taking into account the field of discourse, the semantic context, the deliberative structure, and the rhetorical style. It aims to analyze three hadiths of the Prophet, namely: